MENINGKATKAN MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MAHASISWA PRODI PPKn MELALUI METODE PEMBELAJARAN PROBLEM SOLVING PADA MATAKULIAH PENDIDIKAN BUDI PEKERTI DI UNIVERSITAS PGRI ADI BUANA PSDKU BLITAR - Ekbal Santoso (Bajang Institute, 2022)
The industrial revolution 4.0 and the demands for changes in the 21st century human mindset are very large for the ability to think critically. Learning the concept of character education with problem solving methods can increase the ability to think critically and very critically individually by 28.57% from the first cycle of 57.14% to 100% in the second cycle. As well as the increase in learning outcomes of the concept of character education for Civics students, at least in category B, increased by 92.18% from the first cycle of 7.14% to 100% in the second cycle.